Selective oxidation gold-based catalyst as well as preparation method and application thereof
By preparing the Au-Sca/SibCecXdOe catalyst, the problem of low conversion and yield under low ratio of methanol and methacrylate was solved, and efficient methyl methacrylate synthesis was achieved, improving the selectivity and efficiency of the catalyst.
Patent Information
- Application Number
- CN202310834974.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-07-07
AI Technical Summary
In the prior art, under the low ratio of methanol and methacrylate, the conversion rate of methacrylate and methyl methacrylate yield are relatively low, which has difficulties in preparing catalysts, especially the increase in the reaction selectivity of Au nanoparticles. insufficient.
Provide a selective oxidation gold-based catalyst, including Au-Sca/SibCecXdOe components, to prepare a carrier by mixing Si, Ce, X sources, spray drying, and calcining, and mixing with Au and Sc sources to form a catalyst precursor and optimize the conditions. Dry and calcinate to prepare catalysts with high conversion and high yields.
The high conversion rate of methacrylate and the high yield of methyl methacrylate are achieved, which improves the selectivity and efficiency of the catalyst and is suitable for alkyl acrylate synthesis.
Smart Images

Figure CN119303573A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a selective oxidation gold-based catalyst and a preparation method and application thereof. Background Art
[0002] Methyl methacrylate (MMA), also known as methyl methacrylate, is mainly used as a monomer for organic glass. It is also used in the manufacture of other resins, plastics, coatings, adhesives, lubricants, wood and cork impregnation agents, paper polishes, etc. It is an important organic chemical raw material.
[0003] Among the current industrialized MMA production processes, the traditional ACH method has the characteristics of simple process and high maturity, but the raw material hydrocyanic acid used in this method is highly toxic, and hydrocyanic acid and sulfuric acid are highly corrosive, which places high demands on reaction equipment, and the waste acid discharge is large, which may cause great harm to the environment. The economic benefits of BASF technology are not outstanding, and Alpha technology has just started industrialization, and the technical maturity and overall economic efficiency need to be further tested.
[0004] Using air or oxygen as an oxidant to directly oxidize methacrolein and methanol to the target product MMA is undoubtedly a simple, green and economically competitive process route, because there is no methacrylic acid produced in the middle, and there is no subsequent esterification process of methylpropionic acid and methanol, which will greatly save production costs. At the same time, the by-product of this process is water, which is green and environmentally friendly. However, the difficulty of this process lies in the preparation of the catalyst. Therefore, people have made many efforts to try to solve this problem.
[0005] Currently, oxide-supported precious metal catalysts are mostly used, especially Au-supported catalysts. Au nanoparticles are very beneficial to improving the selectivity of the reaction, but the conversion rate is still significantly insufficient. It is necessary to develop better methyl methacrylate gold-based catalysts to promote the production of methyl methacrylate. Summary of the invention
[0006] The purpose of the present invention is to overcome the problem in the prior art that the conversion rate of methacrolein and the yield of methyl methacrylate are low at a low ratio of methanol to methacrolein, and to provide a selective oxidation gold-based catalyst and a preparation method and application thereof. The catalyst is used for selective oxidation, has a high yield of the target product and a high conversion rate of the raw materials. For example, it is used in the synthesis of alkyl acrylates and has the characteristics of high methacrolein conversion rate and high yield of methyl methacrylate.
[0007] According to a first aspect of the present invention, the present invention provides a selective oxidation gold-based catalyst, the catalyst comprising a component represented by general formula (1):
[0008] Au-Sc a / Si b Ce cX d O e Formula (1)
[0009] In formula (1),
[0010] a is the molar ratio of Sc to Au, and a ranges from 0.1 to 1.0;
[0011] b is the molar ratio of Si to Au, and b ranges from 100 to 500;
[0012] c is the molar ratio of Ce to Au, and the value of c ranges from 1.0 to 30.0;
[0013] d is the molar ratio of X to Au, and the value of d is 0.1 to 2.0;
[0014] e is the number of moles of oxygen atoms required to satisfy the valence of each element in the active component;
[0015] X is at least one selected from Li, Na, K, Rb, and Cs.
[0016] According to a second aspect of the present invention, the present invention provides a method for preparing the selective oxidation gold-based catalyst of the present invention, the method comprising:
[0017] S1. The Si source, Ce source and X source are mixed under solution conditions, allowed to stand for aging, spray dried, and calcined to obtain a carrier;
[0018] S2. Mixing the Au source and the Sc source under solution conditions to obtain a mixed solution I;
[0019] S3. Mixing and contacting the mixed solution I with the carrier to obtain a catalyst precursor, and then optionally drying and calcining.
[0020] According to a third aspect of the present invention, the present invention provides use of the catalyst of the present invention in the synthesis of alkyl acrylates, preferably in the selective oxidation of methacrolein to produce methyl methacrylate.
[0021] The catalyst of the invention is used for selective oxidation, has high yield of target product and high conversion rate of raw materials. For example, when used in the synthesis of alkyl acrylate, it has the characteristics of high conversion rate of methacrolein and high yield of methyl methacrylate. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a TEM image of the selective oxidation gold-based catalyst prepared in Example 1. DETAILED DESCRIPTION
[0023] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0024] The present invention provides a selective oxidation gold-based catalyst, the catalyst comprising a component represented by general formula (1):
[0025] Au-Sc a / Si b Ce c X d O e Formula (1)
[0026] In formula (1),
[0027] a is the molar ratio of Sc to Au, and a ranges from 0.1 to 1.0;
[0028] b is the molar ratio of Si to Au, and b ranges from 100 to 500;
[0029] c is the molar ratio of Ce to Au, and the value of c ranges from 1.0 to 30.0;
[0030] d is the molar ratio of X to Au, and the value of d is 0.1 to 2.0;
[0031] e is the number of moles of oxygen atoms required to satisfy the valence of each element in the active component;
[0032] X is selected from at least one of Li, Na, K, Rb, and Cs. In the embodiments of the present invention, Na is used as an example, but the scope of the present invention is not limited thereto. The catalyst is used for selective oxidation, and has high yield of target product and high conversion rate of raw materials. For example, it is used in the synthesis of alkyl acrylate, and has the characteristics of high conversion rate of methacrolein and high yield of methyl methacrylate.
[0033] According to a preferred embodiment of the present invention, b takes a value of 100 to 500, specifically, for example, 100, 200, 300, 400, 500. In the embodiment of the present invention, 200 is used as an example to illustrate the advantages of the present invention, but the present invention is not limited thereto.
[0034] According to a preferred embodiment of the present invention, c takes a value of 1.0 to 30.0, for example, 1, 5, 10, 15, 20, 25, 30. In the embodiment of the present invention, 10 is used as an example to illustrate the advantages of the present invention, but the present invention is not limited thereto.
[0035] According to a preferred embodiment of the present invention, the ratio of d to c is (0.01-0.5):1, preferably (0.05-0.3):1, more preferably (0.05-0.2):1, further preferably (0.1-0.2):1, for example 0.1:1, 0.15:1, 0.2:1.
[0036] According to a preferred embodiment of the present invention, the particle size of the active components Au and / or Sc of the catalyst is 3-6 nm, and the proportion of 4-5 nm is more than 80%, preferably 85-88%; the average particle size is (4.5-4.7) nm±0.1 nm.
[0037] The composite precious metals of Au and / or Sc in the catalyst of the present invention are evenly distributed and have a narrow size distribution. The particle size is 3-6 nm, of which 4-5 nm accounts for more than 80%, preferably 85-88%; the average particle size is (4.5-4.7) nm±0.1 nm.
[0038] The present invention has no special requirements for the preparation method of the catalyst. The catalyst having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention. According to a preferred embodiment of the present invention, a method for preparing a selective oxidation gold-based catalyst is provided, which comprises:
[0039] S1. The Si source, Ce source and X source are mixed under solution conditions, allowed to stand for aging, spray dried, and calcined to obtain a carrier;
[0040] S2. Mixing the Au source and the Sc source under solution conditions to obtain a mixed solution I;
[0041] S3. Mixing and contacting the mixed solution I with the carrier to obtain a catalyst precursor, and then optionally drying and calcining.
[0042] According to a preferred embodiment of the present invention, the mixing conditions of S1 include: a temperature of 30-40° C. This can further improve the catalytic performance of the catalyst.
[0043] According to a preferred embodiment of the present invention, when the Si source, Ce source and X source are provided in the form of solutions, the temperature of each solution is 30-40° C., and the mixing temperature is 30-40° C. This can further improve the catalytic performance of the catalyst.
[0044] According to a particularly preferred embodiment of the present invention, the mixing step of S1 includes: mixing the Ce source and the X source under solution conditions, and then adding the Si source; preferably, slowly adding the X source solution to the Ce source solution, and then stirring for 10-60 minutes (for example, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes) to obtain a mixed solution M; then slowly adding the Si source solution to the mixed solution M, and then stirring for 10-60 minutes (for example, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes). This can greatly improve the catalytic performance of the catalyst.
[0045] In the present invention, there are no special requirements for the steps and conditions of static aging. For the present invention, preferably, the static aging conditions of S1 include: a time of 12-48 hours (for example, 12 hours, 24 hours, 36 hours, 48 hours), and / or a temperature of 60-120° C. (for example, 60° C., 80° C., 100° C., 120° C.). The use of the above-mentioned preferred static aging conditions can improve the catalytic performance of the catalyst.
[0046] In the present invention, there is no special requirement for the mixing conditions of S2. According to a preferred embodiment of the present invention, the mixing conditions of S2 include: a temperature of 30-40°C.
[0047] According to a preferred embodiment of the present invention, when the Au source and the Sc source are provided in the form of solutions, the temperature of each solution is 30-40°C, and the mixing temperature is 30-40°C.
[0048] In the present invention, there is no special requirement for the mixing step of S2. According to one embodiment, the mixing step of S2 includes: slowly adding the Sc source solution to the Au source solution under stirring conditions, and then stirring for 10-60 minutes.
[0049] In the present invention, there is no special requirement for the mixing and contacting conditions in S3, and preferably includes: after the mixed solution I is mixed with the carrier, stirring is continued at 60-120°C (for example, 60°C, 80°C, 100°C, 120°C) for 30-120min (for example, 30min, 60min, 80min, 100min, 120min).
[0050] In the present invention, the spray drying is performed after the aging is performed and the mixture is stirred evenly.
[0051] In the present invention, there is no special requirement for the spray drying conditions, and the commonly used spray drying conditions can be used in the present invention. For the present invention, the preferred spray drying conditions include: inlet temperature: 150-250°C, outlet temperature 100-140°C.
[0052] In the present invention, there is no special requirement for the source of each component, and commonly used sources of each component can be used in the present invention.
[0053] According to a preferred embodiment of the present invention, the Si source is preferably selected from one or more of silicon powder, silicon dioxide, silica sol, and silicate, and the solid content of the silica sol is preferably 0.5-5% by weight. Silica sol is used as an exemplary description in the embodiments of the present invention, but the scope of the present invention is not limited thereby.
[0054] According to a preferred embodiment of the present invention, the Ce source is preferably selected from one or more of cerium nitrate, ammonium cerium nitrate, and cerium oxide.
[0055] According to a preferred embodiment of the present invention, the X source is preferably selected from one or more of nitrates, carbonates, sulfates, and oxides.
[0056] According to a preferred embodiment of the present invention, the Au source is preferably selected from one or more of chloroauric acid, ammonium tetrachloroaurate, and sodium chloroaurate.
[0057] According to a preferred embodiment of the present invention, the Sc source is preferably selected from one or more of scandium nitrate, scandium sulfate, and scandium trichloride.
[0058] In the present invention, there is no special requirement for the drying and calcining conditions. The drying and calcining conditions commonly used in the art are applicable to the present invention, and the present invention will not be described in detail here.
[0059] According to a preferred embodiment of the present invention, the drying conditions include: 60-120° C., 2-10 h.
[0060] According to a preferred embodiment of the present invention, the calcination conditions include: 350-550° C., 2-10 h.
[0061] The present invention provides application of the catalyst in the synthesis of alkyl acrylate, preferably application of the catalyst in the selective oxidation of methacrolein to prepare methyl methacrylate.
[0062] In the present invention, the purpose of slow operation is to achieve sufficient dissolution.
[0063] The calculation formula of MAL conversion rate (%) includes: conversion rate of methacrolein = methacrolein consumed in the reaction / methacrolein put into the reaction*100%;
[0064] The calculation formula of MMA yield (%) includes: methyl methacrylate yield = methacrolein consumed in producing methyl methacrylate / *methacrolein fed into the reaction.
[0065] In the present invention, when each component source is provided in the form of a solution, there is no special requirement for the content of the component source in the solution, which is generally 0.5 to 5 wt %. The concentration of each solution is not critical to the present invention and will not be described in detail herein. In the embodiment, the concentration of each solution or sol is 2 wt %.
[0066] In the present invention, there is no special requirement for stirring conditions, the purpose is to stir evenly and fully, and the present invention can use magnetic stirring or mechanical stirring.
[0067] Example 1
[0068] 1. Mix the element liquids to obtain the carrier
[0069] Cerium nitrate (molecular formula: Ce(NO 3 ) 3 ), and sodium hydroxide (molecular formula: NaOH) containing 0.015 mol of Na were dissolved in deionized water at 35°C. The sodium hydroxide solution was slowly added to the cerium nitrate solution under stirring, and then stirred for 30 minutes to obtain a mixed solution. Then, silica sol (molecular formula: SiO 2 ) was slowly added to the mixed solution and stirred for 30 minutes. After being mixed evenly, the mixed solution was aged at 80°C for 24 hours. After being stirred evenly, it was spray dried (conditions included: inlet temperature 200°C, outlet temperature 120°C), and calcined at 500°C for 5 hours to obtain the carrier.
[0070] 2. Mixed solution I is obtained
[0071] Chloroauric acid (molecular formula: HAuCl) containing 0.01 mol Au and scandium nitrate (molecular formula: Sc(NO 3 ) 3 ) were dissolved in deionized water at 35°C. The scandium nitrate solution was slowly added to the chloroauric acid solution under stirring, and then the stirring was continued for 30 minutes. After mixing evenly, a mixed solution I was obtained.
[0072] 3. Mix the mixed solution I with the carrier, dry and roast
[0073] The mixed solution I and the carrier were added to a flask, mixed evenly, stirred in an oil bath at 80°C for 60 minutes, and washed after cooling to obtain a catalyst precursor. The catalyst precursor was dried in an oven at 80°C for 3 hours, and then calcined in a muffle furnace at 400°C for 3 hours to obtain a catalyst with the following composition: Au-Sc 0.5 / Si 200 Ce 10 Na 1.5 O e。
[0074] Figure 1 is a TEM image of the selective oxidation gold-based catalyst prepared in Example 1, Figure 1 It can be seen that the composite precious metal particles of Au and / or Sc are evenly distributed, with a particle size of 3 to 6 nm, an average particle size of 4.5 nm, and particles with a size of 4 to 5 nm accounting for 88%.
[0075] Example 2
[0076] The method of Example 1 was followed except that the feed ratio was changed to prepare a catalyst composition of Au-Sc 0.1 / Si 200 Ce 10 Na 1.5 O e The average particle size of the composite precious metal particles of Au and / or Sc in the catalyst is 4.7 nm, and the particle size of 4 to 5 nm accounts for 85%. The results are shown in Table 1.
[0077] Example 3
[0078] The method of Example 1 was followed except that the feed ratio was changed to prepare a catalyst composition of Au-Sc 1.0 / Si 200 Ce 10 Na 1.5 O e The average particle size of the composite precious metal particles of Au and / or Sc in the catalyst is 4.6 nm, and the particle size of 4 to 5 nm accounts for 86%. The results are shown in Table 1.
[0079] Example 4
[0080] The method of Example 1 was followed except that the feed ratio was changed to prepare a catalyst composition of Au-Sc 0.5 / Si 200 Ce 10 Na 0.1 O e The ratio of d to c is 0.01:1. The average particle size of the composite precious metal particles of Au and / or Sc in the catalyst is 4.9 nm, and the particle size of 4 to 5 nm accounts for 81%. The results are shown in Table 1.
[0081] Example 5
[0082] The method of Example 1 was followed except that the feed ratio was changed to prepare a catalyst composition of Au-Sc 0.5 / Si 200 Ce 10 Na 5 O eThe ratio of d to c is 0.5:1. The average particle size of the composite noble metal particles of Au and / or Sc in the catalyst is 4.8 nm, and the particle size of 4 to 5 nm accounts for 80%. The results are shown in Table 1.
[0083] Example 6
[0084] The method of Example 1 was followed, except that the temperature of each solution in step S1 was 50° C. and the mixing temperature was 50° C. The results are shown in Table 1.
[0085] Example 7
[0086] The method of Example 1 is followed, except that the mixing step of S1 is as follows:
[0087] Cerium nitrate (molecular formula: Ce(NO 3 ) 3 ), and sodium hydroxide (molecular formula: NaOH) containing 0.015 mol of Na were dissolved in deionized water at 35°C. The sodium hydroxide solution and cerium nitrate solution were added to 2 mol of Si silica sol (molecular formula: SiO 2 ), and then continued to stir for 60 minutes to obtain a mixed solution; the remaining steps such as standing and aging were the same as in Example 1. The results are shown in Table 1.
[0088] Example 8
[0089] The method of Example 1 is followed, except that no aging is performed.
[0090] Example 9
[0091] The method of Example 1 was followed, except that in step S3, the catalyst drying conditions were 150° C. for 150 min. The results are shown in Table 1.
[0092] Comparative Example 1
[0093] According to the method of Example 1, the feed ratio was changed, and the results are shown in Table 1.
[0094] Comparative Example 2
[0095] The method of Example 1 was followed, except that the feed ratio was changed. The results are shown in Table 1.
[0096] Comparative Example 3
[0097] The method of Example 1 was followed, except that the feed ratio was changed. The results are shown in Table 1.
[0098] Comparative Example 4
[0099] The method of Example 1 was followed, except that the feed ratio was changed. The results are shown in Table 1.
[0100] Table 1
[0101]
[0102] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A selective oxidation gold-based catalyst, characterized in that The catalyst comprises a component represented by the general formula (1): Au-Sc a / And b What c X d A e formula(1) In formula (1), a is the molar ratio of Sc to Au, and a ranges from 0.1 to 1.0; b is the molar ratio of Si to Au, and b ranges from 100 to 500; c is the molar ratio of Ce to Au, and the value of c ranges from 1.0 to 30.0; d is the molar ratio of X to Au, and the value of d is 0.1 to 2.0; e is the number of moles of oxygen atoms required to satisfy the valence of each element in the active component; X is at least one selected from Li, Na, K, Rb, and Cs.
2. The catalyst according to claim 1, wherein The ratio of d to c is (0.01-0.5):1, preferably (0.05-0.3):1, more preferably (0.05-0.2):1, and further preferably (0.1-0.2):1; The particle size of the active components Au and / or Sc of the catalyst is 3-6 nm, and the proportion of 4-5 nm is more than 80%, preferably 85-88%; the average particle size is (4.5-4.7) nm±0.1 nm.
3. A method for preparing a selective oxidation gold-based catalyst according to claim 1 or 2, characterized in that: The method includes: S1. The Si source, Ce source and X source are mixed under solution conditions, allowed to stand for aging, spray dried, and calcined to obtain a carrier; S2. Mixing the Au source and the Sc source under solution conditions to obtain a mixed solution I; S3. Mixing and contacting the mixed solution I with the carrier to obtain a catalyst precursor, and then optionally drying and calcining.
4. The preparation method according to claim 3, wherein The mixing conditions of S1 include: temperature of 30-40°C; When the Si source, Ce source and X source are each provided as a solution, the temperature of each solution is 30-40° C., and the mixed temperature is 30-40° C.; The spray drying conditions include: inlet temperature: 150-250°C, outlet temperature 100-140°C.
5. The preparation method according to claim 3 or 4, wherein The mixing step of S1 includes: mixing the Ce source and the X source under solution conditions, and then adding the Si source; Preferably, the X source solution is slowly added to the Ce source solution, followed by stirring for 10-60 minutes to obtain a mixed solution M; then the Si source solution is slowly added to the mixed solution M, followed by stirring for 10-60 minutes.
6. The preparation method according to any one of claims 3 to 5, wherein: The static aging conditions of S1 include: a time of 12-48 hours, and / or a temperature of 60-120°C.
7. The preparation method according to any one of claims 3 to 6, wherein: The mixing conditions of S2 include: temperature of 30-40°C; When the Au source and the Sc source are provided in the form of solutions, the temperature of each solution is 30-40°C, and the temperature of the mixture is 30-40°C.
8. The preparation method according to any one of claims 3 to 7, wherein: The mixing step of S2 includes: slowly adding the Sc source solution to the Au source solution under stirring conditions, and then stirring for 10-60 minutes.
9. The preparation method according to any one of claims 3 to 8, wherein: The mixed contact conditions in S3 include: after the mixed solution I is mixed with the carrier, stirring is continued at 60-120° C. for 30-120 minutes; Drying conditions include: 60-120°C, 2-10h; The calcination conditions include: 350-550°C, 2-10h.
10. Use of the catalyst according to any one of claims 1 to 2 in the synthesis of alkyl acrylates, preferably in the selective oxidation of methacrolein to produce methyl methacrylate.
Citation Information
Patent Citations
Cs-supported silica-based catalyst and preparation method and application thereof
CN103801280A
Preparation method of catalyst for producing methyl methacrylate and application thereof
CN109331839A
Catalyst for producing furfuryl alcohol, preparation method thereof, and furfuryl alcohol production method
CN109833897A
Application of Au-based catalyst in catalyzing oxidization of aldehyde to produce ester
CN110180541A
Integrated plant for producing 2-ethyl-hexanol and methacrylic acid and a method based thereon
US20070106091A1